Strategi Pengembangan Daya Tarik Wisata Pemandian Pincuran Tujuh Di Kabupaten Sijunjung - Nola Khairani; Yuliana Yuliana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research motivation is the low of tourist attractions development shown by Attraction, Accessibility, Amenity, Ancillary Service at Pincuran Tujuh Bath in Sijunjung Regency. The research purpose is to formulate a way for developing the tourist attraction of Pincuran Tujuh Bath in Sijunjung Regency using SWOT analysis derived from internal factors (strengths and weaknesses) and external factors (opportunities and threats). Overall, the results showed that Pincuran Tujuh Baths has strengths, weaknesses, opportunities, and threats that may be identified for development. Development strategies that can be proposed involve: 1) Development of tourist attractions such as swimming pools for adults and flower gardens or photo areas, by maximizing the utilization of available land. 2) Improving accessibility through the creation of road signs, as well as involving community participation in the road sign creation project. 3) Improved facilities with a focus on safety, comfort, and capacity expansion in the toilet area, rinse room, and parking lot, as well as cooperation with the government for the expansion of existing facilities. 4) Optimal availability of information, security, and promotion centers by utilizing human resources to provide clear information and make visitors feel comfortable while in Pincuran Tujuh Bath.